Development of thin-layer cascades for microalgae cultivation: milestones (review) - Grivalský, Tomáš; Ranglová, Karolína; da Câmara Manoel, João A; Lakatos, Gergely E; Lhotský, Richard; Masojídek, Jiří (Folia microbiologica, 2019)
In this work, the key moments of the development of the so-called thin-layer cascades (TLC) for microalgae production are described. Development started at the end of the 1950s when the first generation of TLCs was set-up in former Czechoslovakia. Since, similar units for microalgae culturing, which are relatively simple, low-cost and highly productive, have been installed in a number of other countries worldwide. The TLCs are characterized by microalgae growth at a low depth (< 50 mm) and fast flow (0.4-0.5 m/s) of culture compared to mixed ponds or raceways. It guarantees a high ratio of exposed surface to total culture volume (> 100 1/m) and rapid light/dark cycling frequencies of cells which result in high biomass productivity (> 30 g/m2/day) and operating at high biomass density, > 10 g/L of dry mass (DW). In TLCs, microalgae culture is grown in the system of inclined platforms that combine the advantages of open systems-direct sun irradiance, easy heat derivation, simple cleaning and maintenance, and efficient degassing-with positive features of closed systems-operation at high biomass densities achieving high volumetric productivity. Among significant advantages of thin layer cascades compared to raceway ponds are the operation at much higher cell densities, very high daylight productivities, and the possibility to store the culture in retention tanks at night, or in unfavourable weather conditions. Concerning the limitations of TLCs, one has to consider contaminations by other microalgae that limit cultivation to robust, fast-growing strains, or those cultured in selective environments.
Keywords: mikrořasy; Bioreactors; Light; Biotechnology; dějiny 20. století; biotechnologie; History, 20th Century; Microalgae; bioreaktory; světlo